SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN KARYAWAN TERBAIK MENGGUNAKAN SIMPLE ADDITIVE WEIGHTING - Beti, Ila Yati (Teknik Informatika Fakultas Ilmu Komputer Univeristas Muslim Indonesia, 2019)
Human Resources is an important asset in the company to be able to achieve company goals, the selection of the best employees is a way that companies do to motivate employee performance. Company leaders usually have difficulty in evaluating employee performance with various assessment indicators available. This results in decisions that are not objective, to be able to process the best employee selection data that is more accurate and more objective results. Then the Decision Support System is needed in the selection of the best employees. In this study there were 25 Alternative Employees who had met the best employee selection requirements that were processed using the Simple Additive Weighting method and based on 5 assessment criteria, namely the criteria of loyalty, responsibility, behavior / ethics, cooperation, and attendance. From the results of the calculation of the SAW method obtained a top 10 ranking and also obtained that employee work loyalty is very influential on the calculation results with a weight of 30% of the overall weight.